Analisis Semiotika Pesan Dakwah dalam Film Horor “Hidayah” - Riska Sari; Andi Adhe Surya Haruna; Andi Dwi Maisarah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The aim of this research is to enhance spiritual awareness, strengthen faith, and encourage people to behave positively. In the horror film